Answer :

Given :

To show :

Formula used : =


If u and v are functions of x,then = u + v

The CHAIN RULE states that the derivative of f(g(x)) is f’(g(x)).g’(x)

y =

squaring on both sides

= + y

Differentiating with respect to x

2y = +

(2y – 1) =

(2y – 1) =

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses